Histone Deacetylase 2 Stabilizes SPARC-related Modular Calcium Binding 2 to Promote Metastasis and Stemness in Gallbladder Cancer - Feng, Ji; Zheng, Xueyong (Current Molecular Medicine, 2025)
BackgroundWe aimed to investigate the relationship between histone deacetylase 2 (HDAC2) and SPARC-related modular calcium binding 2 (SMOC2) and the role of SMOC2 in gallbladder cancer (GBC).MethodsThe expression of HDAC2 and SMOC2 in GBC and normal cells was detected by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR), which was also used to detect the mRNA stability of SMOC2. The combination between HDAC2 and SMOC2 was detected by Chromatin immunoprecipitation (ChIP) assay. After silencing and/or overexpressing HDAC2 and SMOC2, cell viability, migration, invasion, and stemness were respectively tested by the Cell Counting Kit-8 (CCK-8), cell scratch, transwell, and sphere-formation assay.ResultsIn GBC cells, HDAC2 and SMOC2 were highly expressed. HDAC2 combined with SMOC2 promoted mRNA stability of SMOC2. HDAC2 or SMOC2 overexpression promoted GBC cell metastasis and stemness. SMOC2 overexpression rescued the negative effects of silencing HDAC2 in GBC.ConclusionHDAC2 stabilizes SMOC2 to promote metastasis and stemness in gallbladder cancer.
Keywords: metastasis